Overall Survival With Daratumumab, Bortezomib, and Dexamethasone in Previously Treated Multiple Myeloma (CASTOR): A Randomized, Open-Label, Phase III Trial. Issue 8 (22nd November 2022) - Sonneveld, Pieter; Chanan-Khan, Asher; Weisel, Katja; Nooka, Ajay K.; Masszi, Tamas; Beksac, Meral; Spicka, Ivan; Hungria, Vania; Munder, Markus; Mateos, Maria-Victoria; Mark, Tomer M.; Levin, Mark-David; et al.
Abstract : PURPOSE: At the primary analysis of CASTOR (median follow-up, 7.4 months), daratumumab plus bortezomib and dexamethasone (D-Vd) significantly prolonged progression-free survival versus bortezomib and dexamethasone (Vd) alone in relapsed or refractory multiple myeloma (RRMM). We report updated efficacy and safety results at the final analysis for overall survival (OS). METHODS: CASTOR was a multicenter, randomized, open-label, phase III study during which eligible patients with ≥ 1 line of prior therapy were randomly assigned to Vd (up to eight cycles) with or without daratumumab (until disease progression). After positive primary analysis and protocol amendment, patients receiving Vd were offered daratumumab monotherapy after disease progression. RESULTS: At a median (range) follow-up of 72.6 months (0.0-79.8), significant OS benefit was observed with D-Vd (hazard ratio, 0.74; 95% CI, 0.59 to 0.92; P = .0075). Median OS was 49.6 months with D-Vd versus 38.5 months with Vd. Prespecified subgroup analyses demonstrated an OS advantage with D-Vd versus Vd for most subgroups, including patients age ≥ 65 years and patients with one or two prior lines of therapy, International Staging System stage III disease, high-risk cytogenetic abnormalities, and prior bortezomib treatment. The most common (≥ 10%) grade 3/4 treatment-emergent adverse events with D-Vd versus Vd were thrombocytopenia (46.1% v 32.9%), anemia (16.0% v 16.0%), neutropenia (13.6% v 4.6%), lymphopenia (10.3% v 2.5%), and pneumonia (10.7% v 10.1%). CONCLUSION: D-Vd significantly prolonged OS in patients with RRMM, with the greatest OS benefit observed in patients with one prior line of therapy. To our knowledge, our results, together with the OS benefit observed with daratumumab plus lenalidomide and dexamethasone in the phase III POLLUX study, demonstrate for the first time an OS benefit with daratumumab-containing regimens in RRMM (ClinicalTrials.gov identifier: NCT02136134 [CASTOR]).